Poly (lactic-co-glycolic acid)-encapsulated iodine-131 nanoparticles fabricated with rhTSH induce apoptosis and immobilization of thyroid cancer cells - Fan, Yongzeng; Xiong, Yalan; Wang, Xinhong; Chen, Jiahao; Fang, Danzhou; Huang, Jiahui; Yuan, Gengbiao (Frontiers in Oncology, 2023)
Background Aggressive thyroid carcinoma (ATC) usually loses radioiodine avidity to iodine-131 (131I) due to the downregulation of sodium/iodide symporter (NIS). The expression of thyroid stimulating hormone receptor (TSHR) is more persistent than NIS and the administration of recombinant human thyroid stimulating hormone (rhTSH) promotes de novo NIS synthesis. Hence, exploring methods integrating 131I with rhTSH might be a feasible therapeutic strategy for selective delivery of 131I into thyroid cancer to fortify the effect of radioiodine ablation. Methods The 131I, poly (lactic-co-glycolic acid) (PLGA) and rhTSH were used to synthesize of the 131I-PLGA-rhTSH nanoparticles. The characteristics of the 131I-PLGA-rhTSH nanoparticles was determined using a light microscopy, scanning electron microscopy (SEM), autoradiography and immunofluorescence (IF) staining. The diameter of the 131I-PLGA-rhTSH nanoparticles was measured with a Mastersizer 3000, and the encapsulation efficiency (EF) of 131I in 131I-PLGA-rhTSH nanoparticles and the radioactivity of a single nanoparticle were determined. Then, the mouse tumor xenograft model was established, and the biodistribution and effect of 131I-PLGA-rhTSH nanoparticles on apoptosis of thyroid cance cells were investigated in vivo. Thereafter, the role of 131I-PLGA-rhTSH nanoparticles in cell viability using cell counting kit-8 and lactate dehydrogenase (LDH) release assays. Subsequently, the underlying mechanism of 131I-PLGA-rhTSH nanoparticles in reducing cell viability was assessed using immunostaining, boyden invasion assays and phalloidin staining. Results Our results showed that the method of developing nanoparticles-encapsulated 131I using poly (lactic-co-glycolic acid) (PLGA) and modified with rhTSH (131I-PLGA-rhTSH), was a feasible avenue for the integration of 131I and rhTSH. Meanwhile, the encapsulation efficiency (EF) of 131I-PLGA-rhTSH nanoparticles was approximately 60%, and the radioactivity of a single nanoparticle was about 1.1×10-2 Bq. Meanwhile, the 131I-PLGA-rhTSH nanoparticles were selectively delivered into, gradually enriched and slowly downregulated in xenograft tumor after the administration of 131I-PLGA-rhTSH nanoparticles through tail vein in mouse tumor xenograft model. Thereafter, the tumor weight was significantly reduced after the administration of 131I-PLGA-rhTSH nanoparticles. Subsequently, the application of 131I-PLGA-rhTSH nanoparticles facilitated apoptosis and attenuated immobilization via inhibiting F-actin assembling of FTC-133 cells. Conclusion The present study develops a suitable approach integrating 131I and rhTSH, and this strategy is a feasible regimen enhancing the effect of radioiodine ablation for the treatment of thyroid cancer.